Crambe cake protein replacing soybean meal protein and its effects on performance, carcass traits and meat quality of lambs - Marco Antonio Passareli Finardi; Angela Rocio Poveda-Parra; Elzania Sales Pereira; Odimari Pricila Prado-Calixto; Sandra Maria Simonelli; Kassia Amariz Pires; Geisi Loures Guerra; Erica Regina Rodrigues; Ivone Yurika Mizubuti (Journal of Applied Animal Research, 2023)
The objective was to evaluate different levels of crambe cake (CC) protein (0, 250, 500, 750 and 1000 g/kg DM) as a replacement for soybean meal protein in diets for lambs and their effect on performance, carcass traits and meat quality. Forty not castrated crossbred male lambs, weighing 20 ± 3.45 kg, were settled in a completely randomized design with eight replicates per treatment. Final body weight (BW), dry matter intake per kg BW (DMI), DMI over metabolic weight and average daily gain showed linear decreasing effect (p < 0.05), meanwhile, feed efficiency presented a quadratic effect for replacement levels. There was a quadratic effect with replacement levels of CC protein for hot carcass weight; cold carcass weight; cooling loss index; muscle fat thickness; leg perimeter; leg depth and carcass finishing. Hot carcass yield, carcass length; shoulder clods weight, rib weight and the leg weight showed a linear decrease within BW. Bones and muscle weight of shoulder clods showed a decreasing linear effect. Replacing up to 500 g/kg DM of protein of soybean meal protein for CC protein does not affect performance, carcass traits and meat quality.